Brief temperature extremes during wine fermentation: effect on yeast viability and fermentation progress. (27th August 2018) - Valentine, G.D.S.; Walker, M.E.; Gardner, J.M.; Schmid, F.; Jiranek, V.
Abstract: Background and Aims: The impact on viability and metabolic activity of rapid, short‐term exposure of yeast cells to markedly variable temperature is largely unexplored. Fermentation mass loss, flow cytometry using propidium iodide and FUN‐1 yeast viability stains and colony plate counts were used to determine the effect of short‐term temperature changes on yeast cellular metabolism and viability. Methods and Results: Yeast cultures grown at 17 or 30°C were temporarily and rapidly adjusted to near‐freezing or up to 60°C. While near‐freezing conditions had no observable impact on subsequent fermentation activity, exposure to higher temperature did lead to temporary fermentation arrest, loss of viability and metabolic activity. The yeast viability dye FUN‐1 was used to confirm propidium iodide viability measures. Conclusions: Unlike many studies of temperature shifts that used a sustained temperature exposure, this work examined the impact of transient temperature exposures on the wine yeast AWRI 796, as might be encountered during winemaking, and revealed adverse effects even after shifts of only approximately 20 s. Significance of the Study: These findings have implications for yeast management during a wine fermentation, where both refrigeration and heating might be applied to an active fermentation under different circumstances.